2007
DOI: 10.1007/s00018-007-7383-5
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress responses

Abstract: In homeostasis, cellular processes are in a dynamic equilibrium. Perturbation of homeostasis causes stress. In this review I summarize how perturbation of three major functions of the endoplasmic reticulum (ER) in eukaryotic cells -- protein folding, lipid and sterol biosynthesis, and storing intracellular Ca(2+) -- causes ER stress and activates signaling pathways collectively termed the unfolded protein response (UPR). I discuss how the UPR reestablishes homeostasis, and summarize our current understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
529
0
12

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 603 publications
(547 citation statements)
references
References 295 publications
(408 reference statements)
6
529
0
12
Order By: Relevance
“…Pancreatic acinar cells lacking MIST1 lose nearly all ability to secrete digestive enzymes and have significantly increased basal cellular autophagy, characteristics that are found under ER stress conditions as well as in cells lacking Xbp1 (12,21,24,49,50). The observed XBP1-mediated induction of Mist1 during ER stress, coupled with the marked reduction in secretion associated with Mist1 KO acinar cells (12,21), prompted us to investigate if MIST1 might regulate a previously uncharacterized set of gene targets needed for both basal and ER stress-induced maintenance of the secretory machinery.…”
Section: Resultsmentioning
confidence: 99%
“…Pancreatic acinar cells lacking MIST1 lose nearly all ability to secrete digestive enzymes and have significantly increased basal cellular autophagy, characteristics that are found under ER stress conditions as well as in cells lacking Xbp1 (12,21,24,49,50). The observed XBP1-mediated induction of Mist1 during ER stress, coupled with the marked reduction in secretion associated with Mist1 KO acinar cells (12,21), prompted us to investigate if MIST1 might regulate a previously uncharacterized set of gene targets needed for both basal and ER stress-induced maintenance of the secretory machinery.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25][26] The ER stress is generally activated in response to various stressful conditions, such as hypoxia, the accumulation of unfolded or misfolded proteins, the alterations of calcium homeostasis, low glucose levels and others. [8][9][10] Recent reports have shown that ER stress occurs during osteogenic differentiation. [17][18][19][20][21] ER stressinduced apoptosis of osteoblasts has also been implicated in the pathogenesis of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…6a) and 3.3-folds on day 6 with respect to day 1. In comparison, mRNA of GRP94, which binds to partial folded proteins and acts sequentially after GRP78 (Schröder 2008), shows an increase of 2.3-fold on day 3 (Fig. 6b).…”
Section: Early Upregulation Of Chaperones In High Producermentioning
confidence: 95%
“…Homeostasis in ER is maintained by coordinated regulation between three pathways (see Fig. 1): endoplasmic reticulum associated folding (ERAF), ER associated protein degradation (ERAD) and unfolded protein response pathway (UPR) (Schröder 2008). In the event of accumulation of unfolded protein in the ER, the UPR signaling cascade is activated in response to ER stress.…”
Section: Introductionmentioning
confidence: 99%